Haunting of the ghost dragon - West, Tracey, 1965- (West, Tracey, 1965- Dragon Masters, 2024)
Drake and Bo are sent to Gothica to retrieve a powerful dream orb from the castle of the evil wizard Zoltan--but first they must enlist the help of a young dragon master and his ghost dragon, Phantom.